Validation of a de‐immunization strategy for monoclonal antibodies using cynomolgus macaque as a surrogate for human. (10th March 2020) - Kovalova, Natalia; Boyles, Jeffrey; Wen, Yi; Witcher, Derrick R.; Brown‐Augsburger, Patricia L.; Wroblewski, Victor J.; Chlewicki, Lukasz K.
Abstract: The immunogenicity of biotherapeutics presents a major challenge during the clinical development of new protein drugs including monoclonal antibodies. To address this, multiple humanization and de‐immunization techniques that employ in silico algorithms and in vitro test systems have been proposed and implemented. However, the success of these approaches has been variable and to date, the ability of these techniques to predict immunogenicity has not been systematically tested in humans or other primates. This study tested whether antibody humanization and de‐immunization strategies reduce the risk of anti‐drug antibody (ADA) development using cynomolgus macaque as a surrogate for human. First human–cyno chimeric antibodies were constructed by grafting the variable domains of the adalimumab and golimumab monoclonal antibodies onto cynomolgus macaque IgG1 and Igκ constant domains followed by framework germlining to cyno to reduce the xenogenic content. Next, B and T cell epitopes and aggregation‐prone regions were identified using common in silico methods to select domains with an ADA risk for additional modification. The resultant engineered antibodies had a comparable affinity for TNFα, demonstrated similar biophysical properties, and exhibited significantly reduced ADA levels in cynomolgus macaque compared with the parental antibodies, with a corresponding improvement in the pharmacokinetic profile. Notably, plasma concentrations of the engineered antibodies were quantifiable through 504 hours (chimeric) and 840 hours (germlined/de‐immunized), compared with only 336 hours (adalimumab) or 336–672 hours (golimumab). The results point to the significant value in the investment in these engineering strategies as an important guide for monoclonal antibody optimization that can contribute to improved clinical outcomes.